A GaInAs/AlInAs quantum cascade laser with an emission wavelength of 5.6 μm. (May 2018) - Zasavitskii, I.I.; Kovbasa, N.Yu.; Raspopov, N.A.; Lobintsov, A.V.; Kurnyavko, Yu.V.; Gorlachuk, P.V.; Krysa, A.B.; Revin, D.G.
Abstract: A quantum cascade laser based on a strain-compensated Ga0.4 In0.6 As/Al0.58 In0.42 As heteropair is developed, which operates in the pulse regime in the wavelength range of 5.5–5.6 μm at temperatures of up to at least 350 K. It became possible due to an increase in the quantum well depth and to the usage of the two-phonon depopulation mechanism for the lower lasing level. The calculated voltage defect is about 100 meV. The laser epitaxial hetero-structure was grown by the MOVPE method. It was investigated by the high-resolution X-ray diffraction technique. It is shown that the heterostructure has a high quality with bandwidths of main satellite peaks of 55 arcsec. The threshold current density is 1.6 kA cm –2 at 300 К. The characteristic temperature is T 0 = 161 K for the temperature interval of 200 – 350 K. For the laser of size 20 μm × 3 mm with cleaved mirrors, the maximum pulsed power is 1.1 W at 80 K and 130 mW at 300 K. The bibliography includes 13 references.